An Account of Virtue and Solidarity from Pakikipagkapuwa - Cleofas, Jacklyn A (Archīum Ateneo, 2016)
There has been a resurgence of interest among philosophers in Asian conceptions of virtue. In this paper I derive and develop an account of virtue in general, and solidarity in particular, from two Filipino concepts: pakikipagkápuwâ (comradeship with fellow humans) and pakikiramdám (emotional sensitivity). The primary source used for the discussion of these concepts is Filipino psychology, which allows for an account of virtue that is grounded in a particular cultural practice. The ensuing account of virtue, however, is not just contextsensitive; it also showcases an aspect of Filipino culture that has a potential for universality. More specifically, the account of virtue and solidarity from pakikipagkápuwâ and pakikiramdám is shown to have affinities with the interdependent construal of the self, which is discussed by some psychologists; and the relational understanding of autonomy, which is discussed by some philosophers.